Quantification of Linked Column Frame Seismic Performance Factors for Use in Seismic Design. Issue 4 (18th May 2016) - Malakoutian, Mohammad; Berman, Jeffrey W.; Dusicka, Peter; Lopes, Arlindo
Abstract : Previous research has proposed the Linked Column Frame (LCF) as a lateral load-resisting system capable of providing rapid return to occupancy for buildings impacted by moderate earthquake events and collapse prevention in very large events. The LCF consists of flexible moment frames (MF) and linked columns (LC), which are closely spaced dual columns interconnected with bolted links. The linked columns (LC) are designed to limit seismic forces and provide energy dissipation through yielding of the links, while preventing damage to the moment frame under certain earthquake hazard levels. The proposed design procedure ensures the links of the linked column yield at a significantly lower story drift than the beams of the moment frame, enabling design of this system for two distinct performance states: rapid repair, where only link damage occurs and quick link replacement is possible; and collapse prevention, where both the linked column and moment frame may be damaged. Here, the seismic performance factors for the LCF system, including the response modification factor, R, the system over-strength factor, Ω 0, and the deflection amplification factor, Cd, are established following the procedures described in FEMA P695 [2009]. These parameters are necessary for inclusion of the system in the building code. This work describes the development of archetype structures, numerical models of the LCF systems, incremental dynamic analyses, and interpretation of the results. From the results, it is recommended that R, Ω 0, and Cd values of 8, 3, and 5.5 be used for seismic design of the LCF system. A height limit of 35 m (115ft) is recommended at this time as taller LCFs are not considered in this study.